PENGARUH PENERAPAN METODE COLLABORATIVE LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 3 RAMBAH SAMO - -, Supriyanto; Afri, Lusi Eka; -, Hardianto (Universitas Pasir Pengaraian, 2015)
Learning process in the class still use old paradigm, that is teacher become center learning and student tend to accept what their teacher explain. It cause student more passive ad get low achievement in teaching and learning process. So that, we need a learning model which promote students active and provide students the opportunity to develop their potential maximally. Based on the problem above, then apply Metode Collaborative Learning. The purpose of this research was to observe the effect of metode collaborative learning on studentâs mathematic learning outcomes.this research is Quasi experimental with design The Randomized Control Group Only Design. The population in this research were all class 8th grade junior High School 3 Rambah Samo. As a selected sample class is VIII A be experimental class and VIII B be control class. Based on the hypothesis testing performed be t test obtained t = 2,336 and t = 2,01. This means that thitung > ttabel , then H0 is rejected and H1 is accepted. This means that there are differences between the experimental class and the control class. It can be concluded that there are effects of the application of metode collaborative learning to the mathematic learning outcomes of student of 8th grade junior High School 3 Rambah Samo